Improving Student Creative Thinking Skills Through Project Based Learning - Wijayati, Nanik; Sumarni, Woro; Supanti, Sri (KnE Social Sciences, 2019)
The purpose of this study is to improve the ability to think creatively, make pyrolysis devices and make fuel oil from plastic waste. This research is a classroom action research conducted in 3 cycles with the stages of each cycle which includes 4 stages, namely observation, process, observation and reﬂection. The research subjects were students of class XI IPA 3 SMA Negeri 14 Semarang as many as 34 people who entered 12 sons and 22 girls. Data collection uses test instruments and measurement of creative thinking abilities and student response questionnaires. The data were analyzed descriptively and from the results of research that showed ﬂuency, ﬂexibility, originality, and elaboration after the application of hydrocarbon and petroleum learning. The results show that the average way of thinking of students is inthecreativepredicate.withahighincreaseineachindicatorofﬂuencyandelaboration Keywords: creatively; project-based learning; classroom action research.